International Economics and Economic Policy - Welfens, Paul.; Wolf, Holger C.; Richter, Christian; Belke, Ansgar; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The double-blind peer reviewed Journal International Economics and Economic Policy publishes empirical and theoretical contributions, especially papers which are relevant for economic policy. The main focus of the journal is on comparative economic policy, international political economy, including international organizations and policy cooperation, monetary and real/technological dynamics in open economies, globalization and regional integration, trade, migration, international investment, internet commerce and regulation. IEEP particularly offers contributions from the policy community and provides a forum for exchange for the academic and policy community. Officially cited as: Int Econ Econ Policy.
Keywords: Macroeconomics; International economics; Public finance; Economic policy; International Economics; Economic Policy; Macroeconomics/Monetary Economics//Financial Economics; Public Finance; Macroeconomics/Monetary Economics//Financial Economics